Biliary ileus. Peritonitis due to intestinal perforation due to diagnostic paracentesis - Sáez, Hugo; Arriaga, Pedro; Cazabán, Luis A (Cirugía del Uruguay, 1974)
A patíent suffered from multiple biliary íleus; the obstructive gallstone was located in the íleum and two others in the second portian of duodenum. Perforation of a distended loop and consequent peritonitisi complicated diagnostica} punture. In all cases of biliary ileus surgical exploration of gallbladder pole should be performed only when necessary and not as a systematic procedure.